Традиционная народная медицина (народная медицина туркечаре и фольклор) - Хакимова, Нубар (Народна творчість та етнологія, 2014)
Известно, что фольклор в древних устойчивых выражениях выступает как наследие традиционной медицины. Это связано с особенностями, свойственными фольклору. В исследованиях, посвященных народной медицине, эта форма (туркечаре) обрела важное место. It is known that the folklore in the most ancient and steady forms (plots, epics, proverbs, etc.) acts as the heritage of the traditional mytho-poetical era. It should be noted that one important point in studying traditional medicine. In research devoted to traditional medicine, this term covers more wider range of folklore traditions, such as sorcery, plots, signs, spells, ceremonies, etc.